Determinants Of Interest in Using Shopee Pay Later by Kpopers - Kinanti, Sevira; Wijayanti, Anita (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to examine the effect of perceived ease of use, perceived risk, habit, and financial literacy intention to use Shopee pay later by Kpopers, based on two models: Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT). This study applies quantitative approach, utilizing primary data derived from questionnaires. The object of this study including Kpopers purchasing merchandise through Shopee pay later feature. The sample consist of 97 respondents selected through purposive sampling, analyzed by multiple linear regression tests processed by SPSS 25. The test results exhibit that the habit has a positive effect on intention to use Shopee pay later by Kpopers while perceived ease of use, perceived risk, and financial literacy do not have a positive effect on intention to use Shopee pay later by Kpopers.